The Market Quality to Technical Analysis Performance: Intercountry Analysis - Hartono, Jogiyanto; Sulistiawan, Dedhy (Gadjah Mada International Journal of Business, 2014)
The main objective of this research is to discuss the impact of market quality on technical analysis profitability using inter-country analysis. Market quality is proxied by market capitalization. Technical analysis performance (profitability) is calculated using technical analysis return for MA5 indicator and short transaction strategy. This study uses the OSIRIS and Yahoo Finance databases. Using 21 countries with 50 companies for each country, this study finds that market quality affects technical analysis performance. Robustness tests are conducted for longer moving average indicators that are MA10 and MA15. To make sure that the results are not sensitive toward the strategy used, other robustness tests are conducted by using short and long-short transaction strategies. All robustness tests confirm the findings.